Study on physical and structural properties of Neodymium doped lithium boro-tellurite glasses / Ahmad Ridzwan Ab Rahim - Ab Rahim, Ahmad Ridzwan (Faculty Of Applied Sciences, 2018)
Glasses with chemical composition of (70.0)B203-(5.0)TeO2-(25.0-x) Li2C03xNd2O where x = 0, 0.2, 0.4, 0.6, 0.8 and 1.0 mol% are prepared by melt quenching technique. By varying the proportion of Li2C03 and Nd2O3, the effect of this chemical to the lithium boro-tellurite can be investigate in term of physical properties such as density, molar volume and oxygen packing density (OPD). The structural properties were measured by using X-ray Diffraction (XRD) technique and Fourier Tranform Infrared (FTIR) spectroscopy. In this work, generally density and oxygen packing density are found increase while molar volume is decrease as the concentration of neodymium oxide is increases. On the other hand, the amorphous nature was proved by XRD technique and there are presence of Nd-O, Te-O, B-O and OH functional group of glass in FTIR spectra